DISIPLIN KERJA APARATUR SIPIL NEGARA PADA DINAS PERUMAHAN RAKYAT, KAWASAN PERMUKIMAN DAN PERTANAHAN KABUPATEN BANYUASIN - Asri, Asri (Jurnal Ilmiah Bina Manajemen, 2018)
This internship is entitled Work Discipline of the State Civil Apparatus at the Office of Public Housing, Settlements and Land Affairs of the Banyuasin district. The issues raised were how the condition of ASN discipline in the Rakyt Housing Service, the Settlement Area and Land Affairs of the Banyuasin Regency and what factors influenced it. The purpose of this Internship is to find out and analyze how the application of work discipline at the Office of Public Housing, Settlements and Land Affairs Kab. Banyuasin and to find out what factors influence it. The benefits of this Internship are to find out and analyze the factors that can improve ASN's work discipline in the District Housing, Settlement and Land Affairs offices of Kab. Banyuasin., To provide input to the leadership where research on the causes of ASN is not disciplined at work, to address the insights and abilities of the author as well as knowledge of ASN discipline which is the duty of the State Civil Apparatus. The method used in this research is a descriptive qualitative approach: collection data, interviews, observation, documentation and analysis of fish bones (Fishbone Analisys).